A dog death in a hit and run accident - Matos, M. G.; Viana, D. A.; Lopes, C. E. B.; Pimentel, S. P.; Rodrigues, F. R. N. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
The practice of veterinary forensic pathology is often precisely to give a voice to a voiceless animal victim of abuse or neglect and tell a welldocumented story about an animal that has suffered or died (LOCKWOOD, 2016). In human legal medicine, a lot of hit and run cases are the reason for corpse evaluation. The investigation of hit-and-run road accidents is a special challenge to forensic medical examiners requiring a multiskilled approach (FRANÇA, 2015). In the medical literature, the principles of patient evaluation were demonstrated primarily on the basis of hit-and-run fatalities, but they also apply to clinical forensic medicine (DODD, 2000). In forensic necropsies, a multiskilled approach is also needed. It is fundamental to exam carefully all the external and internal bruises, fractures and other signs of trauma and try to link the shapes and severity of damage caused with a hypothesis about the source of the impact suffered by the body (BROWNLIE, 2016). The present paper is a case report of death caused by trauma in consequence of a hit and run, an animal related crime unfortunately not uncommon in veterinary forensic necropsy investigations.